Microglial BDNF, PI3K, and p-ERK in the Spinal Cord Are Suppressed by Pulsed Radiofrequency on Dorsal Root Ganglion to Ease SNI-Induced Neuropathic Pain in Rats. (28th April 2019) - Xu, Xueru; Fu, Shaoxiong; Shi, Xiaomei; Liu, Rongguo
Abstract : Background . Pulsed radiofrequency (PRF) on the dorsal root ganglion (DRG) has been applied to alleviate neuropathic pain effectively, yet the mechanisms underlying pain reduction owing to this treatment are not clarified completely. The activated microglia, brain-derived neurotrophic factor (BDNF), phosphatidylinositol 3-kinase (PI3K), and phosphorylated extracellular signal-regulated kinase (p-ERK) in the spinal cord were demonstrated to be involved in developing neuropathic pain. Also, it has been just known that PRF on DRG inhibits the microglial activation in nerve injury rats. Here, we aim to investigate whether PRF treatment could regulate the levels of BDNF, PI3K, and p-ERK in the spinal cord of rats with spared nerve injury (SNI) via suppressing the spinal microglia activation to ease neuropathic pain. Methods . The rats with SNI were intrathecally treated with minocycline (specific microglia inhibitor) or same volume of dimethyl sulfoxide once daily, beginning from 1 h before nerve transection to 7 days. PRF was applied adjacent to the L4 -L5 DRG of rats with SNI at 45 V for 6 min on the seventh postoperative day, whereas the free-PRF rats were treated without PRF. The withdrawal thresholds were studied, and the spinal levels of ionized calcium-binding adapter molecule 1 (Iba1), BDNF, PI3K, and p-ERK were calculated by western blot analysis, reverse transcription-polymerase chain reaction, and immunofluorescence. Results . The paw withdrawal mechanical threshold and paw withdrawal thermal latency decreased in the ipsilateral hind paws after SNI, and the spinal levels of Iba1, BDNF, PI3K, and p-ERK increased on day 21 after SNI compared with baseline (P < 0.01 ). An intrathecal injection of minocycline led to the reversal of SNI-induced allodynia and increase in levels of Iba1, BDNF, PI3K, and p-ERK. Withdrawal thresholds recovered partially after a single PRF treatment for 14 days, and SNI-induced microglia hyperactivity, BDNF upregulation, and PI3K and ERK phosphorylation in the spinal cord reduced on D14 due to the PRF procedure. Conclusion . Microglial BDNF, PI3K, and p-ERK in the spinal cord are suppressed by the therapy of PRF on DRG to ease SNI-induced neuropathic pain in rats.